EFFECT OF EARTHWORM’S EXTRACTS (APORRECTODEA MOLLERI) ON YEAST GROWTH: IN VITRO STUDY - Houida, S.; Yakkou, L.; Raouane, M.; EL Harti, A.; Amghar, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to investigate the effect of earthworms after their decomposition on yeast growth. To achieve this objective, in vitro crude soluble extracts were prepared from two earthworms lots: freshly harvested from the field “FHE” and the other previously starved for one week “SE”. The dry residues of these two crude extracts were used at different concentrations as a solid media for the growth of two yeast species: one “Candida tropicalis” got from another laboratory and the other was isolated by our team from earthworms’ casts “Filobasidium uniguttulatum”, and their growth was evaluated by colonies counting. The results obtained, compared with the Sabouraud Dextrose Agar (SDA), showed that the growth of both yeast isolates was significantly higher on mediums prepared using exclusively earthworms’ crude extracts and agar. Optimal growth was obtained at a concentration corresponding to 0.375g/100 mL of earthworms’ soluble matter of the two types of earthworms’ lots. These results affirmed the richness and the diversification of those extracts, in nutrients and growth factors, that comes mainly from the intrinsic composition of earthworm’s body biomass. The efficiency of the FHE and SE extracts for cultivation of yeast shows their possible use as a culture media that may be applied to other soil microorganisms and even in vivo as soil amendments or biofertilizers.